2014
DOI: 10.1093/toxsci/kfu122
|View full text |Cite
|
Sign up to set email alerts
|

Different Dose-Dependent Mechanisms Are Involved in Early Cyclosporine A-Induced Cholestatic Effects in HepaRG Cells

Abstract: Mechanisms involved in drug-induced cholestasis in humans remain poorly understood. Although cyclosporine A (CsA) and tacrolimus (FK506) share similar immunosuppressive properties, only CsA is known to cause dose-dependent cholestasis. Here, we have investigated the mechanisms implicated in early cholestatic effects of CsA using the differentiated human HepaRG cell line. Inhibition of efflux and uptake of taurocholate was evidenced as early as 15 min and 1 h respectively after addition of 10μM CsA; it peaked a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 32 publications
8
46
0
Order By: Relevance
“…Moreover, no relevant difference for sinusoidal and canalicular drug transporter protein levels between sandwich-and monolayer-cultured human hepatocytes has been recently demonstrated though LC/MS-MS-based absolute quantification of transporters (Schaefer et al, 2012). Finally, highly-differentiated human hepatoma HepaRG cells exhibit polarized location of main drug transporters associated to taurocholate canalicular secretion, without being cultured in a sandwich configuration (Le Sharanek et al, 2014). Interestingly, a shared component between the culture medium used for our primary human hepatocytes and that used for HepaRG cells is DMSO, which is well known to favor hepatocyte survival and differentiation (Choi et al, 2009;Isom et al, 1985;Noel et al, 2013) and to increase Ntcp and Oatp activity in primary rat hepatocytes (Jigorel et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no relevant difference for sinusoidal and canalicular drug transporter protein levels between sandwich-and monolayer-cultured human hepatocytes has been recently demonstrated though LC/MS-MS-based absolute quantification of transporters (Schaefer et al, 2012). Finally, highly-differentiated human hepatoma HepaRG cells exhibit polarized location of main drug transporters associated to taurocholate canalicular secretion, without being cultured in a sandwich configuration (Le Sharanek et al, 2014). Interestingly, a shared component between the culture medium used for our primary human hepatocytes and that used for HepaRG cells is DMSO, which is well known to favor hepatocyte survival and differentiation (Choi et al, 2009;Isom et al, 1985;Noel et al, 2013) and to increase Ntcp and Oatp activity in primary rat hepatocytes (Jigorel et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…After treatment with DCF ± TNF-α for 30min, 2h, 4h, 8h and 24h, 10 6 cells were incubated for 2h at 37°C with 2µM H2-DCFDA and then washed with cold PBS, and scraped in potassium buffer (10mM, pH 7.4)/methanol (v/v) complemented with Triton X-100 (0.1%). Fluorescence intensity of cell lysates was determined by spectrofluorimetry using excitation/emission wavelengths of 498/520 nm (Sharanek et al, 2014).…”
Section: Determination Of Ros Generationmentioning
confidence: 99%
“…The antioxidant N-acetyl cysteine (NAC) was added to cultures treated with DCF, TNF-α or their combination for 24h at the concentration of 5mM (Fredriksson et al, 2011;Sharanek et al, 2014;Son et al, 2013). Etanercept, a soluble p75 TNF-α receptor that prevents TNF-α to activate its membrane-bound receptor, thereby leading to inhibition of caspase 8 activation via the extrinsic apoptotic pathway (Jouan-Lanhouet et al,…”
Section: Determination Of Caspase 3 8 and 9 Activitiesmentioning
confidence: 99%
“…2014; Sharanek et al. 2014). Interestingly, the investigations performed in HepaRG cells showed that reduced canalicular efflux of taurocholate induced by high concentrations (50  μ mol/L) of cyclosporin were alleviated by 4‐phenylbutyrate (4‐PBA), a chemical chaperone commonly used to protect against ER stress (Sharanek et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, lower concentrations of cyclosporin (10  μ M) impaired taurocholate canalicular efflux without inducing ER stress (Sharanek et al. 2014). Notably, several studies showed that cyclosporin is a potent inhibitor of the bile salt export pump (BSEP) (Dawson et al.…”
Section: Introductionmentioning
confidence: 99%